2013
DOI: 10.1155/2013/792875
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Carbon Nanotube and Nanofiber Based Ethylene‐Octene Copolymer Composites for Thermoelectric Devices

Abstract: Polymer composites have been created from multiwalled carbon nanotubes or carbon nanofibers and ethylene-octene copolymer. The composites have thermoelectric properties and exhibit thermoelectric effect, that is, the conversion of temperature differences into electricity. The thermoelectric efficiency of created composites with nanotube or nanofiber concentration of 30 wt% evaluated by a thermoelectric power at room temperature is 13.3 μV/K and 14.2 μV/K, respectively. The flexible thermoelectric device (therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In our recent article, the flexible thermopile based on the polymeric composites filled with different types of carbon fillers was demonstrated . Moreover, the authors in a very recent paper showed that the thermoelectric power of macroscopic graphene composite varies in a gas environment defined by the molecular mass of adsorbed gas molecules . In other areas such as gas permeation through the CNT membrane, the published data clearly showed that hydrocarbon gases exhibit higher permeability than noncarbohydrates .…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our recent article, the flexible thermopile based on the polymeric composites filled with different types of carbon fillers was demonstrated . Moreover, the authors in a very recent paper showed that the thermoelectric power of macroscopic graphene composite varies in a gas environment defined by the molecular mass of adsorbed gas molecules . In other areas such as gas permeation through the CNT membrane, the published data clearly showed that hydrocarbon gases exhibit higher permeability than noncarbohydrates .…”
Section: Introductionmentioning
confidence: 54%
“…30 Moreover, the authors in a very recent paper showed that the thermoelectric power of macroscopic graphene composite varies in a gas environment defined by the molecular mass of adsorbed gas molecules. 31 In other areas such as gas permeation through the CNT membrane, the published data clearly showed that hydrocarbon gases exhibit higher permeability than noncarbohydrates. 21 Our recent measurements further indicated that the permeation rate can be conveniently stimulated by an electric current.…”
mentioning
confidence: 99%
“…The only exception is MWCNT-PDDA/MWCNT-DOC/PEDOT, which exhibits slightly higher PF than that of CNTY/lignin in the present study, due to the high content of PEDOT, and the combination of LbL assembly with electrochemical polymerization to create synergy capable of producing a high power factor. [16] [27] MWCNT/ PVP Mixing 0.6 [28] PEI/MWCNT/ PVP Mixing 1.98 [28] P3HT/MWCNT Mixing 6 [29] WPU/MWCNT/PEDOT:PSS Mixing 1.41 [30] PEDOT:PSS/MWCNT In situ polymerization 2.29 × 10 −1 [31] MWCNT/Nafion Mixing 0.75 [32] MWCNT-PDDA/MWCNT-DOC/PEDOT LbL + In situ polymerization 155 [16] www.advancedsciencenews.com © 2020 Wiley-VCH GmbH…”
Section: Thermoelectric Propertiesmentioning
confidence: 99%
“…Inorganic nanocomposites have characteristic structures that feature expanded interfaces, quantum effects, and restrained crack propagation. These structures are promising for the improvement of many materials including thermoelectric materials [1][2][3][4][5], photocatalysts [6][7][8][9][10], and structural materials with excellent mechanical properties [11][12][13][14][15][16]. Precise control of the inorganic nanocomposites' morphology [17][18][19][20], size [21][22][23][24], and chemical composition [25][26][27] is very important for these applications.…”
Section: Introductionmentioning
confidence: 99%